(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
In clause features of a plot, an art originality the novel of modern Austrian writer Kristofa Ransmajra «Last world» which is considered one of the best achievements of the literature of a postmodernism are considered.